Interspecies relationships of natural amoebae and bacteria with C. elegans create environments propitious for multigenerational diapause - Marcela Serey; Esteban Retamales; Gabriel Ibañez; Gonzalo Riadi; Patricio Orio; Juan P. Castillo; Andrea Calixto (mSystems)
ABSTRACT The molecular and physical communication within the microscopic world underpins the entire web of life as we know it. However, how organisms, such as bacteria, amoebae, and nematodes—all ubiquitous—interact to sustain their ecological niches, particularly how their associations generate and influence behavior, remains largely unknown. In this study, we developed a framework to examine long-term interactions between microbes and animals. From soil samples collected in a temperate, semi-arid climate, we isolated culturable bacterial genera, including Comamonas, Stenotrophomonas, Chryseobacterium, and Rhodococcus, as well as the amoeba, Tetramitus. This microbial ensemble was fed to the nematode C. elegans in experiments spanning over 20 nematode generations to assess developmental rate, dauer entry, fertility, and feeding behavior. Our findings reveal that microbes and nematodes create a stable environment where no species are exhausted, and where nematodes enter diapause after several generations. We have termed this phenomenon dauer formation on naturally derived ensembles (DaFNE). DaFNE occurs across a range of optimal temperatures, from 15°C to 25°C, and is dependent on the nematode’s pheromone biosynthesis pathway. The phenomenon intensifies with each passing generation, exhibiting both strong intergenerational and transgenerational effects. Moreover, the RNA interference (RNAi) pathway—both systemic and cell-autonomous—is essential for initiating DaFNE, while heritable RNAi effectors are required for its transgenerational effects. These findings indicate that RNA-mediated communication plays a critical role in bacterially induced behaviors in natural environments.IMPORTANCEMicroscopic nematodes are the most abundant multicellular animals on Earth, which implies they have evolved highly successful relationships with their associated microbiota. However, little is known about how nematode behavior is influenced within complex ecosystems where multiple organisms interact. In this study, we used four bacteria and an amoeba from a natural ecosystem to explore behavioral responses in the nematode Caenorhabditis elegans over an 8 week period. The most striking finding was the nematodes’ commitment to a form of hibernation known as diapause. We have termed this phenomenon dauer formation on naturally derived ensembles (DaFNE). Our results suggest that nematodes in nature may frequently enter hibernation as a result of communication with their microbial partners. DaFNE requires the production of nematode pheromones, as well as the RNA interference pathway, indicating that the RNA communication between nematodes and their microbiota may play a critical role. Interestingly, at higher temperatures, fewer animals are needed to trigger DaFNE, suggesting that a mild increase in temperature may promote diapause in natural environments without causing stress to the animals.